2021
DOI: 10.1001/jamanetworkopen.2021.30143
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Subsequent Chronic Diseases Among Middle-aged or Older Adults in China and Associations With Demographic and Socioeconomic Characteristics

Abstract: IMPORTANCE Associations between adverse childhood experiences (ACEs) and chronic diseases among middle-aged or older Chinese individuals have not been well documented. In addition, whether demographic and socioeconomic characteristics modify any such associations has been underexplored. OBJECTIVESTo examine associations between ACEs and subsequent chronic diseases and to assess whether age, sex, educational level, annual per capita household expenditure level, and childhood economic hardship modify these assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
125
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 44 publications
12
125
1
7
Order By: Relevance
“…Sociodemographic variables were obtained from the baseline survey and comprised age, sex, residence (rural or urban), marital status (married/partnered or other), educational level, and current household expenditure per capita. Due to relatively low educational level in Chinese middle-aged and older adults (33.41% of participants had an educational level higher than primary school), we categorised educational level into four groups: illiterate, some primary school, finished primary school, and higher than primary school [ 9 , 26 29 ]. Previous studies suggested that household expenditure per capita had a stronger association with personal well-being and living standards, compared to household income, and therefore was adopted in our analysis to reflect economic status [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sociodemographic variables were obtained from the baseline survey and comprised age, sex, residence (rural or urban), marital status (married/partnered or other), educational level, and current household expenditure per capita. Due to relatively low educational level in Chinese middle-aged and older adults (33.41% of participants had an educational level higher than primary school), we categorised educational level into four groups: illiterate, some primary school, finished primary school, and higher than primary school [ 9 , 26 29 ]. Previous studies suggested that household expenditure per capita had a stronger association with personal well-being and living standards, compared to household income, and therefore was adopted in our analysis to reflect economic status [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is usually comprised of emotional and physical neglect and abuse, household challenges, and other stressful experiences, such as economic hardship, community violence, unsafe neighbourhood, and bullying [ 12 , 13 ]. Exposure to ACEs has been demonstrated to be a risk factor of adverse health conditions in later life, such as ischemic heart disease, cancer, and chronic lung disease [ 12 , 14 ]. There is limited research that has also investigated the link between ACEs and LMS in later life, however, with mixed results [ 8 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also extracted 11 self-reported physician diagnosed diseases from the baseline dataset, including dyslipidaemia, heart disease, stroke, chronic lung disease, asthma, liver disease, cancer, digestive disease, kidney disease, arthritis, and memory-related disease (including Alzheimer’s disease, Parkinson’s disease, and cerebral atrophy). Multimorbidity was defined as the presence of two or more of the above 13 chronic conditions in the same individual [ 27 29 ].…”
Section: Methodsmentioning
confidence: 99%